The Effect Of Work Motivation And Work Discipline On Employee Work Productivity Of Kopi Siloka Tasikmalaya - Miftah, Fahni Saepul; Sutrisna, Arga; Arif (Utami Publisher, 2024)
This study aims to determine the effect of Work Motivation and Work Discipline on Employee Work Productivity of Kopi Siloka Tasikmalaya. The method used is quantitative with a research sample of 30 respondents. The data used are primary and secondary data. The analysis tool used in this study is multiple linear regression analysis using SPSS version 25. Based on the results of this study, it shows that Work Motivation and Work Discipline simultaneously have a positive and significant effect on Work Productivity. Work Motivation partially has a significant effect on Employee Work Productivity. Work Discipline partially has a significant effect on Work Productivity.